2015
DOI: 10.1371/journal.pone.0096102
|View full text |Cite
|
Sign up to set email alerts
|

Fish Intake and Risk of Liver Cancer: A Meta-Analysis

Abstract: BackgroundIncreasing laboratory findings indicate that n-3 fatty acids, mainly derived from fish, inhibit cancer development and progression, but results from epidemiologic studies have been inconsistent and inconclusive.ObjectiveTo evaluate the association of fish intake with risk of liver cancer by conducting a meta-analysis.MethodsPublished case-control/cohort studies that evaluated the relationship between total fish intake and risk of liver cancer were found on PubMed and EMBASE. The pooled relative risks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Most current studies seemed to support a null association for processed meat (53,79,120,121) , or heterocyclic amines (53) , although a positive association between processed red meat and HCC risk was found in the NHS and HPFS (122) . Notably, cohort studies (53,120,122) and the meta-analyses (79,119) consistently suggested a protective association of white meat intake, particularly fish intake with HCC development, which was consistent with the findings form the most recent report by WCRF/AICR (19) . Overall, intake of red meat particularly processed red meat may increase, while white meat possibly fish may decrease the risk of HCC.…”
Section: Meatssupporting
confidence: 87%
See 1 more Smart Citation
“…Most current studies seemed to support a null association for processed meat (53,79,120,121) , or heterocyclic amines (53) , although a positive association between processed red meat and HCC risk was found in the NHS and HPFS (122) . Notably, cohort studies (53,120,122) and the meta-analyses (79,119) consistently suggested a protective association of white meat intake, particularly fish intake with HCC development, which was consistent with the findings form the most recent report by WCRF/AICR (19) . Overall, intake of red meat particularly processed red meat may increase, while white meat possibly fish may decrease the risk of HCC.…”
Section: Meatssupporting
confidence: 87%
“…By contrast, white meats (i.e. poultry and fish), particularly fish intake, have been shown to decrease cancer risk (79,119) , possibly due to long-chain n-3 PUFA present in fish, particularly fatty fish. Also, white meat including fish and poultry is a rich source of BCAA, which may play a protective role in hepatocarcinogenesis (see Section 1.3).…”
Section: Meatsmentioning
confidence: 99%
“…As one important component of diet, fish is considered to be quite healthy, which has been found to be associated with lower risk of all-cause mortality [9], cardiovascular diseases [10] and stroke [11], as well as some forms of cancer, including colorectal [12], lung [13], prostate [14], breast [15], and liver cancers [16]. However, the association between fish intake and brain cancer risk is still inconclusive and inconsistent, and the evidence is scattered.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis is a statistical method that is used to compare and analyze results obtained by and reported in individual scientific studies. It uses statistical methods developed for the purpose of integrating the findings [5]. Hence, meta-analysis allows for the expansion of a pertinent sample, thereby leading to a more accurate interpretation of results.…”
Section: Introductionmentioning
confidence: 99%